Probing the size dependence on the optical modes of anatase nanoplatelets using STEM-EELS. Issue 18 (26th April 2016) - Liberti, Emanuela; Menzel, Robert; Shaffer, Milo S. P.; McComb, David W.
Abstract : Local size dependence of the optical modes of thin anatase nanoplatelets (<5 nm) in response to an electron probe. Abstract : Anatase titania nanoplatelets with predominantly exposed 001 facets have been reported to have enhanced catalytic properties in comparison with bulk anatase. To understand their unusual behaviour, it is essential to fully characterize their electronic and optical properties at the nanometer scale. One way of assessing these fundamental properties is to study the dielectric function. Valence electron energy-loss spectroscopy (EELS) performed using a scanning transmission electron microscope (STEM) is the only analytical method that can probe the complex dielectric function with both high energy (<100 meV) and high spatial (<1 nm) resolution. By correlating experimental STEM-EELS data with simulations based on semi-classical dielectric theory, the dielectric response of thin (<5 nm) anatase nanoplatelets was found to be largely dominated by characteristic (optical) surface modes, which are linked to surface plasmon modes of anatase. For platelets less than 10 nm thick, the frequency of these optical modes varies according to their thickness. This unique optical behaviour prompts the enhancement of light absorption in the ultraviolet regime. Finally, the effect of finite size on the dielectric signal is gradually lost by stacking consistently two or more platelets in a specific crystal orientation, and eventually suppressed for large stacks of platelets.